Anatomical Variables of the Superior Thyroid Artery on Computed Tomography Angiograms - Rodica Narcisa Calotă; Mugurel Constantin Rusu; Marius Ioan Rusu; Cătălin Constantin Dumitru; Alexandra Diana Vrapciu (Medicina)
Background and Objectives: The superior thyroid artery (STA) typically has its origin inferiorly to the greater hyoid horn (GHHB) either from the external carotid artery (ECA) or from the carotid bifurcation (CB) or the common carotid artery (CCA). We aimed to determine the topographic variants of the STA related to the GHHB and the artery of origin and to check their bilateral symmetry. Materials and Methods: Determinations were performed in a sample of 85 archived angio CT adult cases, comprising 53 men and 32 women. The origins of the STAs from the CCA/CB/ECA were classified as types A–C. We defined the vertical topographies of the STA as follows in relation to the GHHB: type 1 (infrahyoid), type 2 (hyoid), and type 3 (suprahyoid). Subtypes of the STA course were added: “a”, lateral to the GHHB; “b”, medial; and “c”, posterior to it. Unilateral combinations of types and bilateral associations of these were established. Results: In 170 carotid axes, we detected STA type A in 8.82%, type B in 28.82%, and type C in 60% of cases. It was absent in 2.35% of the cases. The infrahyoid type 1 of STA was found in 47.06% of cases. The hyoid type 2 was found in 20.59% (2a), 0.59% (2b), and 4.71% (2c). The suprahyoid type 3 was found in 21.18% (3a), 0% (3b), and 3.53% (3c). Thirteen unilateral combinations of types were found. The most prevalent ones were C1 (27.71%), C3a (17.47%), and B1 (15.66%). We established thirty-seven bilateral associations of unilateral combinations of types. The cases with asymmetrical bilateral associations of unilateral combinations of types prevailed. A lowered hyoid bone overlapping the thyroid cartilage was found in one of these cases. The prevailing associations were C1-C1 (bilateral infrahyoid origin of the STA from the ECA, 13/85, 15.29%), C3a-C3a (suprahyoid origins of the STAs from the ECAs and lateral courses over the GHHB, 9/85, 10.58%) and C1-B1 (infrahyoid origins from the ECA and CB, 8/85, 9.41%). Conclusions: The vertical topography of the STA is highly variable and hardly predictable but can be examined in imaging studies. The GHHB may be of use to identify and manage the artery. The STA is rarely absent.